Genotypic Variation in Plant Traits, Chemical Defenses, and Resistance Against Insect Herbivores in Avocado (Persea americana) Across a Domestication Gradient - Hernández-Cumplido, Johnattan; Rodriguez-Saona, Cesar; Ruíz-Rodríguez, Claudia E.; Guevara-Fefer, Patricia; Aguirre-Paleo, Salvador; Miranda Trejo, Serafín; Callejas-Chavero, Alicia (Frontiers in Agronomy, 2021)
Domestication promotes divergence between wild and cultivated plants. The “plant domestication-reduced defense” hypothesis proposes that cultivated plants have lower chemical defenses and resistance against herbivores than their wild counterparts. Yet, the effects of domestication on the interactions between perennial crops and insect herbivores have not been well documented. In this study, we hypothesized that domesticated avocado (Persea americana) has lowered resistance against insect herbivores. To test this hypothesis, we measured variation in plant traits (fruit and seed size, seed germination, and plant growth), chemical defenses (total phenolics), and resistance against two leaf-chewing insect herbivores—a specialist (Copaxa multifenestrata) and a generalist (Spodoptera frugiperda)—among seven avocado genotypes across a domestication gradient: wild (ancestral) genotypes, five (intermediate) landraces (‘Blanco’, ‘Lonjas’, ‘Vargas’, ‘Zarcoli’, and ‘Rodolfo’), and the cultivated (modern) ‘Hass’. Our results showed that seeds from ‘Hass’ have a lower germination rate and slower growth and have shorter fruits and seeds than the landraces and wild genotypes. ‘Hass’ leaves also had lower amounts of total phenolics than the landraces; however, no differences were found between ‘Hass’ and the wild genotypes. There was no effect of genotype on larval mass gained for both herbivores. However, C. multifenestrata had longer larval longevity on ‘Hass’ and the wild genotypes, whereas S. frugiperda larval longevity showed no differences among genotypes. Moreover, C. multifenestrata inflicted more damage on ‘Hass’, whereas S. frugiperda inflicted more damage on ‘Lonjas’ than on the other genotypes. In general, bigger fruit and seeds were positively correlated with plant size and phenolic content, and total phenolics were positively correlated with S. frugiperda and negatively correlated with C. multifenestrata larval performance. However, despite the genotypic variation in plant traits, phenolic content, and resistance against two herbivores with different levels of specialization, there was no clear support for the “plant domestication-reduced defense” hypothesis in avocado.